2019
DOI: 10.5897/jpbcs2018.0768
|View full text |Cite
|
Sign up to set email alerts
|

Development and screening of cowpea recombinant inbred lines for seedling drought tolerance

Abstract: The use of multiple traits for drought study affirms the complexity of drought tolerance in cowpea. Despite the availability of several traits for drought tolerance evaluation, the rapid screening technique used by many scientists for seedling drought in wooden boxes is the simplest method for screening large populations. The objective of this study was to select drought tolerant cowpea recombinant lines developed from a drought tolerant and susceptible parent using the wooden box screening technique. Two hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Wilting is the external manifestation of water potential in plants. It has been proved that leaf wilting is closely related to the plant drought resistance and can be an indicator for the evaluation of plant drought resistance ( Alidu et al, 2019 ; Ye et al., 2020 ), scores based on the leaf wilting were also used for genome-wide association analysis in biotic ( Paulino et al., 2021 ) or abiotic ( Ahmed et al., 2021 ) stress research. To assess the drought resistance of highland barley directly and accurately, the wilting rate of qingkes under drought stress was counted and divided into 0 to 4 grades.…”
Section: Resultsmentioning
confidence: 99%
“…Wilting is the external manifestation of water potential in plants. It has been proved that leaf wilting is closely related to the plant drought resistance and can be an indicator for the evaluation of plant drought resistance ( Alidu et al, 2019 ; Ye et al., 2020 ), scores based on the leaf wilting were also used for genome-wide association analysis in biotic ( Paulino et al., 2021 ) or abiotic ( Ahmed et al., 2021 ) stress research. To assess the drought resistance of highland barley directly and accurately, the wilting rate of qingkes under drought stress was counted and divided into 0 to 4 grades.…”
Section: Resultsmentioning
confidence: 99%
“…Our main aim was to identify seedling drought tolerant lines and genotypic components of the seedling responses to drought stress. The wooden box technique has been shown in previous studies to be useful for evaluating a large number of genotypes such as Recombinant inbred lines (RILs) and landraces (Agbicodo et al, 2009;Alidu et al, 2019;Cui et al, 2020;Ravelombola et al, 2018Ravelombola et al, , 2020Verbree et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some tomato accessions were shown to maintain slightly greater levels of chlorophyll content under drought stress as compared to others, indicating potential differences in drought tolerance among the accessions. Alidu et al and Cardoso et al [38,61] also reported moderately greater leaf chlorophyll content in drought-tolerant cowpea recombinant inbred line and tomato genotypes, respectively, subjected to dry conditions. Furthermore, the report by Monteoliva et al [58] indicates that plants exhibiting more elevated chlorophyll levels than their counterparts under optimal water availability conditions are anticipated to exhibit greater tolerance.…”
Section: Spad Chlorophyll Contentmentioning
confidence: 94%